Preliminary Study of Tagged MR Image Velocimetry in a Replica of an Intracranial Aneurysm - Isoda, Haruo; Inagawa, Shoichi; Takeda, Hiroyasu; Isogai, Satoshi; Takehara, Yasuo; Sakahara, Harumi (American Journal of Neuroradiology, 2003)
Summary: Flow dynamics in intracranial aneurysms and their adjacent parent vessels play important roles in the development and rupture of intracranial aneurysms. Combined with tagged MR imaging and the use of particle image velocimetry software, tagged MR image velocimetry reveals flow vectors, vorticity, and shear strains at each location in the aneurysm replica every 9 milliseconds. This technique is a promising and noninvasive technique for assessing hemodynamics in intracranial aneurysms.